2023
DOI: 10.3390/antibiotics12020393
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Clinical Outcomes of Molnupiravir for the Treatment of Mild to Moderate COVID-19 in Adult Patients during the Dominance of the Omicron Variant: A Meta-Analysis

Abstract: Introduction: The therapeutic impact of molnupiravir in the Omicron variant phase is unknown. The goal of the current meta-analysis was to compare the real-world clinical outcomes of molnupiravir for the treatment of mild to moderate COVID-19 during the dominance of the Omicron variant in adult patients to that of a placebo. Methods: To be included, studies had to directly compare the clinical effectiveness of molnupiravir in treating adult COVID-19 patients to that of a placebo. Studies were included based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…According to this meta‐analysis, the all‐cause hospitalization rate was statistically lower in the nirmatrelvir/ritonavir‐treated patients compared to those receiving molnupiravir. Meta‐analyses 6,7 revealed that both treatments can reduce the admission to the hospital due to COVID‐19 disease. However, real‐world studies 14,28 on nonhospitalized COVID‐19 patients showed that nirmatrelvir/ritonavir‐treated patients are less likely to be hospitalized compared to the molnupiravir‐receiving ones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to this meta‐analysis, the all‐cause hospitalization rate was statistically lower in the nirmatrelvir/ritonavir‐treated patients compared to those receiving molnupiravir. Meta‐analyses 6,7 revealed that both treatments can reduce the admission to the hospital due to COVID‐19 disease. However, real‐world studies 14,28 on nonhospitalized COVID‐19 patients showed that nirmatrelvir/ritonavir‐treated patients are less likely to be hospitalized compared to the molnupiravir‐receiving ones.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published meta‐analyses 6,7 indicated the higher effectiveness of nirmatrelvir/ritonavir and molnupiravir in improving the mortality rate of patients with COVID‐19 compared to the controls. The present meta‐analysis demonstrated that treatment of COVID‐19 with nirmatrelvir/ritonavir is associated with a statistically lower rate of mortality compared to those treated with molnupiravir.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted among U.S. veterans aged 65 years and older, receipt of molnupiravir was associated with a lower 30-day risk of hospitalization or death (RR 0.67, 95% CI 0.46 to 0.99), but the overall result between treated and untreated patients was similar [16]. The meta-analysis by Huang et al, which included six studies involving 89,480 patients (22,355 of whom received molnupiravir therapy and 67,125 of whom received placebo therapy), indicated that the risk of mortality was reduced by 34% and the risk of the composite outcome of disease progression was reduced by 37% among patients who received molnupiravir [17].…”
Section: Discussionmentioning
confidence: 99%